The message of Plato : a re-interpretation of the Republic - Urwick, E. J. (Edward Johns), 1867-1945 (Routledge library editions. Plato, 2012)
Edward Urwick's original work draws upon Plato's best known work, the Republic, to provide a new interpretation of Plato's teaching based upon Indian religious thought. Most scholars have sought to interpret the Republic from the standpoint of politics, ethics, and metaphysics and indeed the accepted title of the dialogue - Concerning a Polity or Republic - would seem to legitimate this. Even the alternative title for the work - Concerning Justice - seems to justify such an approach. Yet the original Greek work, Dikaiosune, had a fuller meaning: righteousness. The author believes this gives.